Silicon nitride sintered body, insulation circuit board, and semiconductor device
Patent Information
- Application Number
- JP2024224609
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-26
- Estimated Expiration
- 2043-08-22
AI Technical Summary
【0023】 本発明の窒化ケイ素焼結体は、EBSD法によるβ型窒化ケイ素結晶粒の集合組織特性を制御することにより、および/または、X線回折法による結晶特性を制御することによって、特性異方性を改善することを可能とした。
Smart Images

Figure 2025041757000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a silicon nitride sintered body, an insulating circuit board, and a semiconductor device. [Background technology]
[0002] In recent years, the heat density of power modules has increased with the increasing density and power output of electronic devices and semiconductor devices. The temperature rise of a power module can cause malfunction of elements and cracks in an insulated circuit board. For this reason, ceramic substrates such as alumina and aluminum nitride, which are materials with relatively high thermal conductivity, have been used for insulated circuit boards. However, alumina and aluminum nitride have the disadvantage of low mechanical strength. Therefore, thick copper, which is subject to strong thermal stress, cannot be directly bonded to a ceramic substrate, which has restricted the structure of power modules. Specifically, a problem is that a heat sink (metal plate) such as copper or aluminum needs to be soldered to an insulated circuit board, which leads to an increase in the size of the power module. Therefore, silicon nitride (Si3N4) material has been attracting attention as an insulated circuit board. Since silicon nitride sintered bodies have higher strength and fracture toughness than alumina and aluminum nitride sintered bodies, it is possible to directly bond thick copper to an insulated circuit board, which contributes to the miniaturization of modules. For this reason, silicon nitride sintered bodies with improved mechanical strength and thermal conductivity are being developed.
[0003] For example, Patent Document 1 discloses a method for producing a silicon nitride sintered body substrate with improved mechanical properties and thermal conductivity. In this method, 1 to 15% by weight of a sintering aid of one or more elements selected from Mg, Ca, Sr, Ba, Y, La, Ce, Pr, Nd, Sm, Gd, Dy, Ho, Er, and Yb is added to silicon nitride powder containing 0.1% by weight or less of Al, and the resulting mixture is molded and then fired at a temperature of 1700°C to 2300°C under a nitrogen gas pressure of 1 to 500 atm. The silicon nitride sintered body substrate obtained by this method is composed of 85% to 99% by weight of β-type silicon nitride grains and the remainder being a grain boundary phase of oxide or oxynitride. The grain boundary phase contains 0.5% to 10% by weight of one or more metal elements selected from Mg, Ca, Sr, Ba, Y, La, Ce, Pr, Nd, Sm, Gd, Dy, Ho, Er, and Yb. The grain boundary phase contains 1% by weight or less of Al atoms, has a porosity of 5% or less, and in the microstructure of the sintered body, the proportion of β-type silicon nitride grains having a minor axis diameter of 5 μm or more is 10% to 60% by volume. In other words, it is known that in order to obtain a silicon nitride sintered body substrate with high thermal conductivity, rare earth compounds and magnesium oxide are added as sintering aids, and the thermal conductivity and mechanical strength can be improved by changing the mixing ratio and amount of them. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 9-30866 Summary of the Invention [Problem to be solved by the invention]
[0005] It is known that the β-type silicon nitride crystal grains, which are the main crystalline phase of silicon nitride sintered bodies, are columnar crystal grains elongated in the c-axis direction. Therefore, silicon nitride sintered bodies do not consist of completely random crystal grain orientation, but often show a crystal phase distribution in which the crystal grains are oriented in a specific direction depending on the grain size, shape, molding method, etc. of the raw material. The bias in the orientation of the crystal grains in the silicon nitride sintered body causes anisotropy in the properties of the thermal conductivity and bending strength of the silicon nitride sintered body. Specifically, it is known that β-type silicon nitride crystal grains have anisotropy in thermal conductivity in the a-axis and c-axis directions, but the bias in the orientation of the crystal grains in a specific direction causes anisotropy in the thermal conductivity of the silicon nitride sintered body. In addition, the crystal grain orientation in a specific direction also affects the compounding of β-type silicon nitride crystal grains, and the change in the deflection and elongation of the cracks causes anisotropy in the mechanical strength. In particular, in doctor blades and extrusion molding, which generate shear forces during molding, even if the amount of added β-type silicon nitride crystal grains is small, the crystal grains are oriented in the molding direction when the slurry flows, which causes a large anisotropy between the molding direction and the direction perpendicular to the molding direction. On the other hand, the reaction sintering method, which uses Si powder as a raw material, also causes anisotropy problems. When producing sintered bodies using the reaction sintering method, the exothermic reaction during nitriding causes local melting of Si and the progress of β-type silicon nitride, which makes the properties of the sintered body more likely to become uneven. For this reason, it is common to control the nitriding reaction by adding silicon nitride powder as a diluent when mixing the raw materials, but the silicon nitride powder added at this time affects the crystal grain orientation of the sintered body, resulting in the crystal grains being preferentially oriented in a specific direction. It is desirable to mitigate the property anisotropy of such silicon nitride sintered bodies, as it may affect the device design depending on the device application.
[0006] The inventors reviewed the conventional manufacturing methods for silicon nitride sintered bodies and focused on controlling the texture structure of the silicon nitride sintered bodies, with the aim of suppressing the anisotropy of properties such as the thermal conductivity and bending strength of the silicon nitride sintered bodies.
[0007] In order to solve the above problems, an object of the present invention is to provide a silicon nitride sintered body in which the anisotropy of properties such as thermal conductivity and bending strength is alleviated. A further object of the present invention is to provide an insulating circuit board and a semiconductor device using the silicon nitride sintered body. [Means for solving the problem]
[0008] One embodiment of the silicon nitride sintered body of the present invention is characterized in that the texture index J, which indicates the distribution state of the crystal orientation of each crystal grain, obtained from texture analysis of β-type silicon nitride crystal grains on the substrate surface by EBSD method, is 1.2 to 1.7.
[0009] The silicon nitride sintered body of one embodiment of the present invention is characterized in that, when the substrate thickness direction is taken as the ND direction, and the crystal orientation distribution obtained from the texture analysis of β-type silicon nitride crystal grains on the substrate surface by the EBSD method is expressed in terms of Euler angles (φ1, Φ, φ2) defined by Bunge, the maximum value of the density profile (MUD) in the ranges of φ2=0°, Φ=0°, and φ1=0 to 60° is 1.0 to 1.6, and the maximum value of the density profile (MUD) in the ranges of φ2=0°, Φ=90°, and φ1=0 to 180° is 2.0 to 7.0.
[0010] One embodiment of the silicon nitride sintered body of the present invention is characterized in that, when the substrate thickness direction is taken as the ND direction, the area ratio of β-silicon nitride crystal grains having a crystal orientation in which the inclination of the {1 0 -1 0} plane of the β-silicon nitride crystal grains from the ND direction is within 70° in a pole figure obtained from texture analysis of the β-silicon nitride crystal grains on the substrate surface by the EBSD method is 90 to 98% with respect to all β-silicon nitride crystal grains.
[0011] One embodiment of the silicon nitride sintered body of the present invention is characterized in that, when the thickness direction of the substrate is taken as the ND direction, the area ratio of β-silicon nitride crystal grains having a crystal orientation in which the inclination of the {1 0 -1 0} plane of the β-silicon nitride crystal grains from the ND direction is within 60° in a pole figure obtained from texture analysis of the β-silicon nitride crystal grains on the substrate surface by the EBSD method is 80 to 94% with respect to all β-silicon nitride crystal grains.
[0012] One embodiment of the silicon nitride sintered body of the present invention is characterized in that, when the thickness direction of the substrate is taken as the ND direction, the area ratio of β-silicon nitride crystal grains having a crystal orientation in which the inclination of the {1 0 -1 0} plane of the β-silicon nitride crystal grains from the ND direction is within 50° in a pole figure obtained from texture analysis of the β-silicon nitride crystal grains on the substrate surface by the EBSD method is 65 to 85% with respect to all β-silicon nitride crystal grains.
[0013] A silicon nitride sintered body according to one embodiment of the present invention is characterized in that, when the thickness direction of the substrate is taken as the ND direction, the area ratio of β-type silicon nitride crystal grains having a crystal orientation in which the inclination of the {1 0 -1 0} plane of the β-type silicon nitride crystal grains from the ND direction is within 40° in a pole figure obtained by analyzing the texture of the β-type silicon nitride crystal grains on the substrate surface by the EBSD method is 50 to 75% relative to all the β-type silicon nitride crystal grains.
[0014] One embodiment of the silicon nitride sintered body of the present invention is characterized in that, when the substrate thickness direction is taken as the ND direction, the area ratio of β-silicon nitride crystal grains having a crystal orientation in which the inclination of the {1 0 -1 0} plane of the β-silicon nitride crystal grains from the ND direction is within 30° in a pole figure obtained from texture analysis of the β-silicon nitride crystal grains on the substrate surface by the EBSD method is 30 to 52% with respect to all β-silicon nitride crystal grains.
[0015] The silicon nitride sintered body of one embodiment of the present invention is characterized in that, when the substrate thickness direction is taken as the ND direction, the intensity ratio I(002) / I(200) of the integrated intensity I(002) of the X-ray diffraction peak corresponding to the Miller index (002) plane of a β-type silicon nitride crystal grain in the ND direction, obtained by substrate surface analysis using an X-ray diffraction method, to the integrated intensity I(200) of the X-ray diffraction peak corresponding to the Miller index (200) plane, is 0.05 to 0.2.
[0016] A silicon nitride sintered body according to a further embodiment of the present invention is further characterized in that the ratio (|λz-λx| / λx) of the difference between the thermal conductivity λz in the thickness direction of the substrate and the thermal conductivity λx in the substrate molding direction to the thermal conductivity λx in the substrate molding direction is 6% or less.
[0017] The silicon nitride sintered body according to a further embodiment of the present invention is further characterized in that the thermal conductivity λz in the thickness direction of the substrate and the thermal conductivity λx in the molding direction of the substrate are each 70 W / mK or more.
[0018] A further form of the silicon nitride sintered body of the present invention is characterized in that the bending strength σx in the substrate molding direction within the substrate surface perpendicular to the substrate thickness direction and the bending strength σy in the direction perpendicular to the substrate molding direction are each 600 MPa or more, and the ratio of the difference between the bending strength σx and the bending strength σy to the bending strength σx (|σy-σx| / σx) is 10% or less.
[0019] A further embodiment of the silicon nitride sintered body of the present invention is further characterized in that, in a plane perpendicular to the substrate thickness direction, the ratio (|λx-λy| / λx) of the difference between the thermal conductivity λx in the substrate molding direction and the thermal conductivity λy in a direction perpendicular to the substrate molding direction to the thermal conductivity λx in the substrate molding direction is 1.5% or less.
[0020] The silicon nitride sintered body according to a further embodiment of the present invention is further characterized in that the bending strength in two orthogonal axial directions in a plane orthogonal to the substrate thickness direction is 600 MPa or more, and the ratio of the bending strength in the two axial directions is 0.9 to 1.1. The two axial directions may be the molding direction and a direction orthogonal to the molding direction.
[0021] A silicon nitride sintered body according to a further embodiment of the present invention is further characterized in that the silicon nitride sintered body contains, in terms of a raw material mixing ratio, 92.5 to 97 weight % of Si3N4, 2.0 to 4.5 weight % of Y2O3, and 1.0 to 3.0 weight % of MgO.
[0022] An insulating circuit board according to one embodiment of the present invention is characterized by comprising a silicon nitride sintered body having the above-mentioned characteristics and a metal plate bonded to a surface of the silicon nitride sintered body. Also, a semiconductor device according to one embodiment of the present invention is characterized by comprising the insulating circuit board described above and a semiconductor element mounted on the metal plate of the insulating circuit board. Effect of the Invention
[0023] The silicon nitride sintered body of the present invention makes it possible to improve the property anisotropy by controlling the texture characteristics of the β-silicon nitride crystal grains by EBSD method and / or by controlling the crystal characteristics by X-ray diffraction method. [Brief description of the drawings]
[0024] [Figure 1] FIG. 2 shows band contrast images obtained by EBSD for the silicon nitride sintered bodies of Example 1, Example 2, Comparative Example 1, and Comparative Example 3. [Diagram 2] 3 is a {1 0 -1 0} pole figure obtained by EBSD for the silicon nitride sintered bodies of Example 1, Example 2, Comparative Example 1, and Comparative Example 3. [Diagram 3] 4 is a crystal orientation distribution map at φ2=0° obtained by EBSD method for the silicon nitride sintered bodies of Example 1, Example 2, Comparative Example 1, and Comparative Example 3. [Figure 4]4 is a graph showing density profiles in the ranges of φ2=0°, Φ=0°, and φ1=0 to 60° of the silicon nitride sintered bodies of Example 1, Example 2, Comparative Example 1, and Comparative Example 3 in the crystal orientation distribution of FIG. [Diagram 5] 4 is a graph showing density profiles in the ranges of φ2=0°, φ=90°, and φ1=0 to 180° of the silicon nitride sintered bodies of Example 1, Example 2, Comparative Example 1, and Comparative Example 3 in the crystal orientation distribution of FIG. [Figure 6] 1 is an SEM image (magnification: 5000) of pulverized β-type silicon nitride sintered powder in the manufacturing process of the silicon nitride sintered body of the present invention. [Figure 7] 1 is a schematic diagram showing a semiconductor device according to an embodiment of the present invention; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] The silicon nitride sintered body according to one embodiment of the present invention has a substrate shape of a predetermined thickness, and can be used as a substrate for mounting electronic components by brazing (brazing or soldering) a metal plate such as a copper plate to the substrate surface. The thickness of the substrate is preferably 0.1 to 1.0 mm. Here, in the silicon nitride sintered body substrate, the substrate thickness direction is the ND or Z direction (the normal direction to the substrate surface), the forming (or rolling) direction in the plane (substrate surface) perpendicular to the ND direction is the RD or X direction, and the direction perpendicular to the RD direction in the plane (substrate surface) perpendicular to the ND direction is the TD or Y direction.
[0026] The silicon nitride sintered body of this embodiment may be composed of a silicon nitride sintered body containing 1 to 5 weight % of rare earth oxide (first sintering aid), 1.0 to 3.5 weight % of magnesium compound (second sintering aid), and the remainder being Si3N4. That is, the silicon nitride sintered body of this embodiment is formed by molding and firing a slurry mixture of raw material powders in which silicon nitride powder, rare earth oxide powder, and magnesium oxide powder are mixed in a predetermined blending ratio. The silicon nitride sintered body may be formed by a reaction sintering method using Si powder as the main raw material.
[0027] In this embodiment, the sintering aid is a combination of an oxide of a rare earth element (Y, La, Ce, Pr, Nd, Sm, Gd, Dy, Ho, Er, Yb) as the first sintering aid and magnesium oxide (MgO) or magnesium silicon nitride (MgSiN2) as the second sintering aid. In particular, by adding a Mg component together with a rare earth oxide as the sintering aid component, the liquid phase generation temperature during sintering can be lowered and sinterability can be improved. Furthermore, it is more preferable that the first sintering aid is 2.0 to 4.5 wt % Y2O3 and the second sintering aid is 1.0 to 3.0 wt % MgO. It has been known from past findings that the use of Mg and Y as the sintering aid components makes the silicon nitride sintered body dense, and as a result, it is possible to achieve both relatively high thermal conductivity and mechanical strength. In this embodiment, MgO and Y2O3 are adopted as the sintering aid. Furthermore, as an additional additive, an appropriate amount of hafnium oxide (HfO2) may be added to further promote crystallization of the grain boundary phase. It has been previously found that the rare earth oxide composition ratio within the range of 1 to 5 weight % does not significantly affect the properties of the silicon nitride sintered body substrate, so a person skilled in the art can freely select the type and composition ratio.
[0028] The β-type silicon nitride crystal grains (or particles) constituting the substrate of the silicon nitride sintered body have a crystal structure in the shape of a long and thin hexagonal column having a long axis and a short axis. The silicon nitride sintered body of this embodiment is designed to reduce the anisotropy of the thermal conductivity and / or mechanical strength characteristics by controlling the random orientation of the β-type silicon nitride crystal grains.
[0029] The silicon nitride sintered body of this embodiment has a specific range of texture characteristics obtained by texture analysis of β-silicon nitride crystal grains on the substrate surface by EBSD method when the substrate thickness direction is set as the ND direction. In other words, the inventors have found that in a silicon nitride sintered body having a texture structure in a certain specific range, the anisotropy of properties such as thermal conductivity and bending strength is alleviated. In other words, by controlling the texture characteristics of the β-silicon nitride crystal grains in the silicon nitride sintered body, a desired silicon nitride sintered body with alleviated property anisotropy can be obtained.
[0030] The EBSD (Electron Back-Scatter Diffraction) method uses a scanning electron microscope to measure the orientation of individual crystal grains and microscopic regions, making it possible to analyze the microscopic texture of a silicon nitride sintered body substrate. In particular, the EBSD method obtains orientation information for each crystal grain at a measurement depth of about several tens of nm from the substrate surface, making it possible to quantitatively evaluate the texture and the corresponding crystal orientation. In this embodiment, the following texture characteristics are used to control the characteristic anisotropy of the silicon nitride sintered body.
[0031] Texture index J The EBSD map obtained by the EBSD method was subjected to orientation distribution function (ODF) analysis to obtain the texture index J, which indicates the distribution of the crystal orientation of each crystal grain. The texture index J indicates how strong the texture of the sample (i.e., the state in which crystals are arranged in a specific orientation) is, and indicates 1 when the distribution of the crystal orientation is completely random and indicates a value of infinity when all the crystal orientations are the same (e.g., single crystal).
[0032] In the ODF analysis, the spherical harmonic function T by Bunge is used. l mn (g) Using the series expansion method, we obtain the following series expansion:
number
number
[0033] -Density profile using Euler angles (φ1, Φ, φ2) (multiples of uniform density, MUD) Texture analysis using the EBSD method includes a method of directly plotting the obtained crystal orientation in a three-dimensional space with the Euler angles (φ1, Φ, φ2) defined by Bunge as the coordinate axes. In this method, one plotted point can definitively represent the crystal orientation, so it is a strict representation of the crystal orientation. In this method, the crystal orientation is expressed in the form of (hkl)[uvw] using the index of the crystal plane perpendicular to the ND direction (hkl) and the index of the crystal direction parallel to the RD direction [uvw], and the Euler angles corresponding to each crystal orientation are plotted in Euler space. In the case of a hexagonal crystal system such as β-Si3N4, the distribution of {0 0 0 1} planes in Euler space can be quantitatively evaluated by taking the orientation distribution in the section from φ1=0° to 60° at φ2=0° and Φ=0°, and the ratio of grains whose major axis of β-Si3N4 is oriented in the ND direction. Similarly, the distribution of {1 0 -1 0} planes can be quantitatively evaluated as a density profile by taking the orientation distribution in the section from φ1=0° to 180° at φ2=0° and Φ=90°. The texture characteristics were evaluated by the maximum value of the density profile.
[0034] Pole figures The texture analysis by EBSD method includes evaluation of pole figures showing the distribution of the crystal orientation of the {1 0 -1 0} plane of β-Si3N4 crystal grains in the RD-TD plane, which is a plane perpendicular to the ND direction. In the pole figures, the areas with a high distribution density of the {1 0 -1 0} plane are shown in white, and the lower the distribution density, the darker the color. The texture characteristics were quantitatively evaluated by the area ratio of β-type silicon nitride crystal grains in the pole figures that have a crystal orientation tilted within a certain angle range from the ND direction to the {1 0 -1 0} plane of the β-type silicon nitride crystal grains. This area ratio is also called the cumulative relative frequency of the tilt angle range of the {1 0 -1 0} plane of the β-Si3N4 crystal grains with respect to the ND direction.
[0035] The silicon nitride sintered body of this embodiment has the following specific texture characteristics with respect to the texture index J. The texture index J, which indicates the distribution state of the crystal orientation of each crystal grain, is 1.2 to 1.7, preferably 1.2 to 1.64, more preferably 1.2 to 1.58, and further preferably 1.2 to 1.53.
[0036] The silicon nitride sintered body of this embodiment has the following specific texture characteristics with respect to the density profile. The density profile is visually illustrated by the crystal orientation distribution diagram of Fig. 3. The maximum value of the density profile (MUD) in the range of φ2 = 0°, Φ = 0°, and φ1 = 0 to 60° is 1.0 to 1.6, preferably 1.0 to 1.53, more preferably 1.06 to 1.50, and even more preferably 1.14 to 1.50, and the maximum value of the density profile in the range of φ2 = 0°, Φ = 90°, and φ1 = 0 to 180° is 2.0 to 7.0, preferably 2.0 to 6.38, more preferably 2.1 to 6.38, and even more preferably 2.10 to 4.26.
[0037] The silicon nitride sintered body of this embodiment is illustrated by the pole figure in FIG. 2, and has the following specific texture characteristics by quantitative evaluation of the pole figure. The area ratio of β-type silicon nitride crystal grains having a crystal orientation in which the inclination of the {1 0 -1 0} plane of the β-type silicon nitride crystal grain from the ND direction is within 70° is 90 to 98%, preferably 91 to 98%, more preferably 91.4 to 97.8%, and even more preferably 94.9 to 97.8% of all β-type silicon nitride crystal grains. The area ratio of β-type silicon nitride crystal grains having a crystal orientation in which the inclination of the {1 0 -1 0} plane of the β-type silicon nitride crystal grain from the ND direction is within 60° is 80 to 94%, preferably 81 to 94%, more preferably 81.3 to 93.3%, and even more preferably 85.7 to 93.3% of all β-type silicon nitride crystal grains. The area ratio of β-silicon nitride crystal grains having a crystal orientation in which the {1 0 -1 0} plane of the β-silicon nitride crystal grain is inclined from the ND direction by 50° or less is 65 to 85%, preferably 67 to 84%, more preferably 67.5 to 83.1%, and even more preferably 70.2 to 83.1% of all β-silicon nitride crystal grains. The area ratio of β-silicon nitride crystal grains having a crystal orientation in which the {1 0 -1 0} plane of the β-silicon nitride crystal grain is inclined from the ND direction by 40° or less is 50 to 75%, preferably 51 to 73%, more preferably 51.8 to 72.1%, and even more preferably 51.8 to 68.1% of all β-silicon nitride crystal grains. The area ratio of β-type silicon nitride crystal grains having a crystal orientation in which the inclination of the {1 0 -1 0} plane of the β-type silicon nitride crystal grain from the ND direction is within 30° is 30 to 52%, preferably 33 to 52%, more preferably 34.1 to 51.1%, and even more preferably 34.1 to 48.3% of all β-type silicon nitride crystal grains.
[0038] That is, the silicon nitride sintered body of the present embodiment has the above texture characteristics, and thus has a texture structure in which β-type silicon nitride crystal grains are randomly oriented.
[0039] The silicon nitride sintered body of this embodiment has the following characteristics regarding thermal conductivity in relation to the above texture characteristics. The thermal conductivity λx in the substrate molding direction (RD direction), the thermal conductivity λy in the direction perpendicular to the substrate molding direction (TD direction), and the thermal conductivity λz in the substrate thickness direction (ND direction) are each 70 W / mK or more. The ratio of the difference between the thermal conductivity λz and the thermal conductivity λx in the substrate thickness direction to the thermal conductivity λx (|λz-λx| / λx) is 6% or less. In addition, the ratio of the difference between the thermal conductivity λx and the thermal conductivity λy to the thermal conductivity λx (|λx-λy| / λx) is within 1.5%. This means that the ratio of the difference in thermal conductivity in any two orthogonal axial directions in a plane perpendicular to the substrate thickness direction is within 1.5%. This is because the difference between the thermal conductivity λx and the thermal conductivity λy is maximum in the plane. That is, the silicon nitride sintered body of this embodiment has high thermal conductivity characteristics with a thermal conductivity of 70 W / mK or more, and further, the anisotropy of the characteristics is relaxed to 6% or less.
[0040] The silicon nitride sintered body of this embodiment has the following mechanical strength characteristics in relation to the texture characteristics. The bending strength σx in the substrate molding direction (RD direction) and the bending strength σy in the direction perpendicular to the substrate molding direction (TD direction) are each 600 MPa or more. The ratio of the difference between the bending strength σx and the bending strength σy to the bending strength σx (|σx-σy| / σx) is within 10%. This means that the ratio of bending strengths in any two orthogonal axial directions in a plane perpendicular to the substrate thickness direction is 0.9 to 1.1. This is because the difference between the bending strength σx and the bending strength σy is maximum in the plane. That is, the silicon nitride sintered body of this embodiment has high mechanical strength characteristics with a bending strength of 600 MPa or more, and further, the characteristic anisotropy is relaxed to 10% or less.
[0041] Therefore, the silicon nitride sintered body of this embodiment has both a thermal conductivity of 70 W / mK or more and a bending strength of 600 MPa or more, and furthermore, it is possible to suppress the characteristic anisotropy to 6% or less and 10% or less, respectively.
[0042] The silicon nitride sintered body of this embodiment was also analyzed by substrate surface analysis using X-ray diffraction. That is, it was found that the silicon nitride sintered body has the following crystal structure characteristics in relation to the above-mentioned texture characteristics. When the substrate thickness direction is the ND direction, the intensity ratio I(002) / I(200) between the integrated intensity I(002) of the X-ray diffraction peak corresponding to the Miller index (002) plane of the β-type silicon nitride crystal grain in the ND direction obtained by substrate surface analysis using X-ray diffraction and the integrated intensity I(200) of the X-ray diffraction peak corresponding to the Miller index (200) plane is 0.05 to 0.2 when the substrate thickness direction is the ND direction.
[0043] Next, a method for producing the silicon nitride sintered body of this embodiment will be described. The method for producing the silicon nitride sintered body mainly includes a step of producing a silicon nitride ingot with a β ratio of 70 to 90%, a step of crushing the silicon nitride ingot to produce a β-type silicon nitride powder having a specific surface area and average particle size in a predetermined range, a step of mixing the β-type silicon nitride powder, rare earth oxide powder, and magnesium oxide powder (or magnesium silicon nitride powder) in a predetermined compounding ratio and adding a solvent to form a slurry, a step of forming the slurry into a sheet molded body of a predetermined thickness, and a step of sintering the sheet molded body in a non-oxidizing atmosphere to obtain a silicon nitride sintered body. Each step will be described in detail below.
[0044] First, β-type silicon nitride powder was synthesized by a direct nitridation method. Metallic silicon powder was mixed with magnesium oxide powder (0.2 wt% to 1.0 wt% relative to the metallic silicon powder) and a nitridation reaction was carried out at a temperature of 1350°C or higher to obtain a silicon nitride ingot with a β ratio of 70 to 90%. The obtained ingot was then coarsely crushed and finely crushed to obtain a silicon nitride ingot with a specific surface area of 6.0 to 11.0 m, which did not contain columnar grains with a minor axis diameter of 2 μm or more. 2The specific surface area was adjusted to within the range of 0.5 μm to 1.5 μm, and the average particle diameter D50 was adjusted by the grinding time. The powder after grinding was then washed with acid and water to adjust the oxygen content to 0.8% or less and the surface fluorine content to 800 ppm or less. Although the adjusted β-type silicon nitride powder contains a small amount of whiskers, it does not contain columnar particles with a minor axis diameter of 2 μm or more, and the majority of the particles are polygonal (see Figure 6). This makes it possible to obtain a sintered body in which no specific crystal plane is oriented during molding and which remains relatively unoriented even after sintering.
[0045] 2-4.5 wt% of rare earth oxide powder (preferably yttrium oxide powder) and 1.0-3.0 wt% of magnesium oxide powder (or magnesium silicon nitride powder) were wet mixed in a mixed solvent of toluene and ethanol using a ball mill with φ10 silicon nitride balls and a nylon pot mill. In the wet mixing, an appropriate amount of dispersant may be added, and typically, a polycarboxylic acid-based or amine-based dispersant is added at a concentration of 0.2 mg / m2 relative to the surface area of the raw material powder. 2 to 1.5 mg / m 2 The remaining β-type silicon nitride powder is put into the mill and mixed for 12 to 24 hours. Then, a binder, a plasticizer, and an organic solvent are added to make a slurry. As a method for preparing the slurry used for molding, wet mixing using an organic solvent is desirable in order to suppress productivity and an increase in the amount of oxygen during mixing. As a specific example, a dispersant, an organic solvent containing toluene and ethanol is added to the raw material powder, and the slurry is prepared by a commonly used mixing and grinding method. Then, the mixture is uniformly mixed and the particle size is adjusted by a method such as a ball mill, a bead mill, and a vibration mill. The slurry is degassed and the viscosity is adjusted in a vacuum, and the viscosity is adjusted to a degree that allows the green sheet to be molded. The mill and media used in the mixing and grinding method can be made of resins such as urethane and nylon, or ceramics such as silicon nitride and zirconium oxide, but it is preferable to use resins or silicon nitride as the materials to prevent impurities from being mixed into the slurry.
[0046] The rare earth oxide powder may be selected from the oxides of Y, La, Ce, Pr, Nd, Sm, Gd, Dy, Ho, Er, Yb, or combinations thereof. Preferably, the rare earth oxide powder is yttrium oxide (Y2O3).
[0047] In addition, β-type silicon nitride powder has a specific surface area of 11.0 m 2 / g or less, and using only rare earth oxides as sintering aids does not result in sufficient densification. Therefore, it is desirable to use magnesium compounds such as magnesium oxide (MgO) and magnesium silicon nitride (MgSiN2) and rare earth oxides such as Yb2O3 and Y2O3 as sintering aids. Magnesium compounds form liquid phase compounds with low melting points, which have the effect of promoting densification, lowering the sintering temperature, and shortening the sintering time. In addition, rare earth oxides have a high affinity for oxygen, which reduces the amount of dissolved oxygen in silicon nitride particles and increases thermal conductivity.
[0048] In the molding process, the high-viscosity slurry after viscosity adjustment by vacuum degassing is molded into a sheet, and a green sheet of a specified thickness is obtained by the doctor blade method. The thickness of the green sheet can be appropriately changed depending on the required thickness of the sintered body, but is usually in the range of about 0.1 to 1.3 mm. The molded green sheet is processed into a desired shape by a mold press or a cutting machine to obtain a molded body. In this molding process, the direction in which the doctor blade moves relatively to roll the molded body is determined as the molding direction (RD direction) of the silicon nitride sintered body.
[0049] The surface of the green body obtained in the molding process is sprayed with boron nitride powder as a mold release agent, and a block body is prepared by stacking 15 to 30 green bodies. The block body is placed in a boron nitride sheath and degreased in dry air at a temperature range of 500 to 600°C. The degreasing atmosphere may be nitrogen or a vacuum. The degreased block body is fired at a high temperature for a predetermined time to obtain a silicon nitride sintered body, which is the final object of this manufacturing method. The firing process is performed in a firing furnace in a non-oxidizing (nitrogen) atmosphere at a temperature range of about 1750 to 2000°C. In addition, in order to prevent volatilization of Si3N4 and sintering aids (e.g., MgO), it is preferable to perform pressurized firing under a pressure of 5 atmospheres or more.
[0050] By going through the steps described above, a silicon nitride sintered body substrate having specific texture characteristics can be obtained.
[0051] As a second embodiment, the silicon nitride sintered body may be formed by a reaction sintering method using Si powder as the main raw material. As in the above manufacturing method, a silicon nitride ingot is pulverized to produce β-type silicon nitride powder having a specific surface area and average particle size within a predetermined range. The produced β-type silicon nitride powder is then added to the Si powder as a diluent during raw material mixing to obtain a silicon nitride sintered body substrate having the above texture characteristics. The β-type silicon nitride powder is preferably 3 to 10% by weight.
[0052] FIG. 7 is a schematic diagram illustrating an insulating circuit board 11 configured using the silicon nitride sintered body of the above embodiment, and a semiconductor device 10 including the insulating circuit board 11. The insulating circuit board 11 includes a silicon nitride sintered body 13 formed as an insulating board, and a metal plate 15 as a conductor (circuit) bonded to the surface of the silicon nitride sintered body 13. In the example of FIG. 7, the metal plate 15 is bonded to both the upper and lower surfaces of the silicon nitride sintered body 13 via a bonding layer. Here, the metal plate 15 is preferably a copper plate. In addition, the bonding layer is preferably a solder material such as Ag nanoparticles. The semiconductor device 10 includes the insulating circuit board 11 and a semiconductor element 17 mounted on the metal plate 15 of the insulating circuit board 11. The semiconductor element 17 is mounted using solder paste or the like. That is, the semiconductor device 10 of this embodiment can exhibit the characteristics of the silicon nitride sintered body 13 with improved characteristic anisotropy as a semiconductor device product. EXAMPLES
[0053] The present invention will be described in more detail below based on examples and comparative examples, but the present invention should not be construed as being limited to the following examples.
[0054] The silicon nitride sintered bodies according to Examples 1 to 8 and Comparative Examples 1 to 3 were produced under the following conditions and procedures. In Examples 1 to 8 and Comparative Example 3, a metal ingot synthesized from high-purity metal silicon powder by a direct nitriding method was crushed and washed to prepare a β-type silicon nitride powder. The specific surface area and average particle size of the β-type silicon nitride powder were measured to confirm its characteristics. Next, in Examples 1 to 7 and Comparative Example 3, appropriate amounts of MgO powder and Y2O3 powder were added to the β-type silicon nitride powder in accordance with the blending composition ratio of each powder. Furthermore, in Example 7, an appropriate amount of HfO2 powder was added. In Example 8, appropriate amounts of the prepared β-type silicon nitride powder, MgSiN2 powder, and Y2O3 powder were added to the metal silicon powder in accordance with the blending composition ratio of each powder. In Comparative Examples 1 and 2, appropriate amounts of MgO powder and Y2O3 powder were added to the metal silicon powder in accordance with the blending composition ratio of each powder. For 100 parts by weight of this mixture, a polycarboxylic acid-based surface-active dispersant was added at 0.3 mg / m 2Then, about 50 parts by weight of a mixed solvent of toluene and ethanol was added, and the mixture was ground and mixed using silicon nitride balls. Then, 18 parts by weight of polyvinyl butyral as a binder, 6 parts by weight of dioctyl adipate as a plasticizer, and about 20 parts by weight of a mixed solvent of toluene and ethanol were added, and the mixture was stirred and mixed by a ball mill until the binder was completely dissolved and mixed, and a slurry was prepared. Then, the slurry was left in a vacuum, and the viscosity was adjusted by degassing and volatilizing. Next, a sheet molded body was obtained from the prepared slurry by a doctor blade method. The molding direction of the doctor blade was determined as the substrate molding direction X. The obtained sheet molded body was punched into a shape of 260 mm x 200 mm by die pressing. Then, boron nitride powder was sprayed as a mold release agent on the surface of the punched sheet, and 25 laminates were prepared per block, which were then placed in a boron nitride sheath and heated to 500 ° C. in dry air for about 4 hours to remove organic components such as the binder. The sheet compact was then heated in a nitrogen atmosphere at 9 atm for 4 hours at 1860°C to obtain a silicon nitride substrate stack. The silicon nitride substrate stack was separated, the top and bottom substrates were removed, and the peripheries of the remaining 23 substrates were broken using a laser. The boron nitride powder remaining on the substrate surfaces and the droplets that had adhered to the substrate by the laser processing were then removed by honing to obtain a silicon nitride sintered substrate measuring 190mm x 140mm x 0.32mm.
[0055] At the preparation stage of each sample, the specific surface area, particle diameter D50, fluorine content, and oxygen content of the β-type silicon nitride powder were measured. Then, for each prepared sample, texture analysis was performed using the EBSD method to obtain the texture index J, crystal orientation distribution diagram at φ2=0°, maximum value of the density profile, maximum value, pole figure, and area ratio in the pole figure. In addition, for each prepared sample, structure analysis was performed using the X-ray diffraction method to obtain the intensity ratio I(002) / I(200). For each prepared sample, the thermal conductivity λx in the substrate molding direction, the thermal conductivity λy in the direction perpendicular to the substrate molding direction, and the thermal conductivity λz in the substrate thickness direction were measured. In addition, for each prepared sample, the bending strength σx in the substrate molding direction and the bending strength σy in the direction perpendicular to the substrate molding direction were measured.
[0056] Various measurements and evaluations were performed under the following conditions.
[0057] ·Specific surface area of β-type silicon nitride powder The specific surface area was measured by the BET single point method using a Monosorb MS-21 made by Quantachrome.
[0058] ·β-type silicon nitride powder particle size D50 The measurements were carried out using a laser diffraction particle size distribution analyzer SALD-2000 manufactured by Shimadzu Corporation. Sodium hexametaphosphate was used as the dispersant, with a refractive index of 2.4.
[0059] ·Fluorine content of β-type silicon nitride powder The measurements were performed using the pyrohydrolysis separation-ion chromatography method described in JIS R 1603 (2018) using an ion chromatograph Dionex Integrion RFIC manufactured by Thermo Fisher Scientific Inc. and an automatic sample combustion apparatus AQF-2100H manufactured by Nitto Seiko Analytech Co., Ltd.
[0060] ·Oxygen content of β-type silicon nitride powder The measurements were carried out by inert gas fusion-non-dispersive infrared absorption spectrometry using an EMGA-920 manufactured by Horiba Ltd.
[0061] Texture analysis using EBSD method The crystal orientation of each sample was measured by EBSD using a C-Nano model manufactured by Oxford Instruments. The measurement surface was mirror-finished by the following method. First, the surface was flattened using a #600 diamond polishing pad. Then, intermediate polishing was performed using diamond slurry in the order of 15 μm, 6 μm, and 1 μm. For final polishing, the surface was polished with 50 nm alumina slurry, followed by polishing with 40 nm colloidal silica to obtain a mirror surface. After final polishing, the surface was ultrasonically cleaned using acetone and ethanol, and the surface roughness Sa in the range of 100 μm x 140 μm (objective lens magnification: 100 times) was 0.01 μm or less using a laser microscope. The sample coordinate system was set so that the thickness direction of the substrate after mirror finishing was the Z direction (ND direction), the substrate forming direction was the X direction (RD direction), and the direction perpendicular to the substrate forming direction was the Y direction (TD direction). 2 EBSD mapping was performed on the area of the sample. The obtained EBSD map was analyzed using the EBSD analysis tool AZtecCrystal from Oxford Instruments to perform orientation distribution function analysis, etc., to obtain the texture index J, the crystal orientation distribution diagram at φ2 = 0°, the maximum value of the density profile, the maximum value, the pole figure, and the area ratio of the pole figure.
[0062] X-ray diffraction measurement and analysis The X-ray diffraction intensity of each sample was measured by powder X-ray diffraction method using Cu-Kα radiation using an Ultima IV model manufactured by Rigaku Corporation. Individual pieces cut to 15 mm x 15 mm were used for the measurement. The substrate surface was polished to 20 μm or more with a #600 diamond polishing pad, and the surface roughness Sa of 0.6 μm or less in an area of 100 μm x 140 μm (objective lens magnification: 100 times) measured by a laser microscope was used as the measurement surface. The X-ray diffraction measurement conditions were as follows. Scan range: 10 degrees to 85 degrees Sampling width: 0.02 degrees Scan speed: 10 degrees / min Divergence slit: 2 / 3 degree Divergence vertical slit: 10mm Scattering slit: 8mm Receiving slit: open Tube voltage / current: 40kV / 40mA Detector: Semiconductor detector In the X-ray diffraction pattern of the substrate plane obtained by irradiating X-rays on the substrate plane, the integrated intensities of the diffraction peaks corresponding to the Miller indices (002) and (200) of β-type silicon nitride particles were calculated using analysis software.
[0063] Thermal conductivity The flash method was used to measure the thermal conductivity of the substrate in various directions. A thermal conductivity measuring device LFA467 manufactured by NETZSCH Geratebau GmbH was used for the measurements. Pieces cut to 10 mm x 10 mm from the substrate were used for the measurements. A gold sputtered film of approximately 100 nm was formed on both sides of the pieces to reduce the transmission of flash light, and graphene spray was used on both sides of the pieces to uniformly absorb the pulsed light, with the graphene coating amount being approximately 0.1 mg / mm. 2 A uniform blackening treatment was performed so that the thermal conductivity in the X and Y directions was measured using a sample holder for in-plane measurements. When calculating the thermal conductivity, a value of 0.68 J / (g K) was used as the specific heat of the obtained sintered body.
[0064] 3-point bending strength The measuring device was an AG-IS model manufactured by Shimadzu Corporation, and the measurement conditions were a crosshead speed of 0.5 mm / min, a support distance of 30 mm, and the size of the test piece was 20 mm wide and 0.3 to 0.4 mm thick. The bending strength σx in the X direction was tested with the test jig placed perpendicular to the forming direction (the support distance direction of the support coincides with the X direction), and the bending strength σy in the Y direction was tested with the test jig placed parallel to the forming direction (the support distance direction of the support coincides with the Y direction).
[0065] Tables 1 and 2 show the conditions and various measurement results for each sample of Examples 1 to 8 and Reference Examples 1 to 3. Table 1 mainly shows the preparation conditions of each sample, and Table 2 shows various characteristics. FIG. 1 shows representative band contrast images of Examples 1 and 2 and Comparative Examples 1 and 3 by EBSD method. FIG. 2 shows representative pole figures of Examples 1 and 2 and Comparative Examples 1 and 3 by EBSD method. FIG. 3 shows representative crystal orientation distribution diagrams at φ2=0° of Examples 1 and 2 and Comparative Examples 1 and 3. FIG. 4 shows representative density profiles in the range of φ2=0°, Φ=0°, and φ1=0 to 60° of Examples 1 and 2 and Comparative Examples 1 and 3. FIG. 5 shows representative density profiles in the range of φ2=0°, Φ=90°, and φ1=0 to 180° of Examples 1 and 2 and Comparative Examples 1 and 3.
[0066] [Table 1]
[0067] [Table 2]
[0068] According to Table 1, Examples 1 to 7 are 6.0 to 11.0 m 2 The main raw material was a β-type silicon nitride powder having a specific surface area of 5.0 m / g and an average particle size D50 of 0.5 μm to 1.5 μm. On the other hand, in Example 8, metal silicon powder was used as the main raw material, but β-type silicon nitride powder in the above range was added as a diluent. In contrast, Comparative Examples 1 and 2 used metal silicon powder as the main raw material without adding a diluent. Comparative Example 3 was formed using a β-type silicon nitride powder having a specific surface area of 5.0 m / g and an average particle size D50 of 0.5 μm to 1.5 μm. 2 The material was made from β-type silicon nitride powder with a specific surface area of 1.0 μm / g and an average particle size D50 of 2.0 μm.
[0069] As shown in Table 2, the texture index J is 1.2 to 1.7 in Examples 1 to 8, whereas it is larger than 1.7 in Comparative Examples 1 to 3. This indicates that the crystal grains in Examples 1 to 8 are more randomly oriented than those in Comparative Examples 1 to 3. In addition, the maximum value of the density profile in the range of φ2=0°, Φ=0°, and φ1=0 to 60° in Examples 1 to 8 is 1.0 to 1.6, and the maximum value of the density profile in the range of φ2=0°, Φ=90°, and φ1=0 to 180° is 2.0 to 7.0, whereas Comparative Examples 1 to 3 show values outside the above ranges. That is, Examples 1 to 8 and Comparative Examples 1 to 3 can be differentiated in terms of texture characteristics by the maximum value of the density profile as well.
[0070] Furthermore, according to the pole figures in Fig. 2, in Examples 1 and 2, white areas are dispersed, and the crystal orientation of the β-Si3N4 crystal grains is dispersed over a wide range. On the other hand, in Comparative Example 1, the distribution in the Z direction (the intersection of the X and Y axes) is extremely small, and it is understood that the {0 0 0 1} plane of the β-Si3N4 crystal grains is preferentially oriented in the Z direction (ND direction). Also, in Comparative Example 3, the distribution of the {1 0 -1 0} plane in the Y direction is large, and it is understood that the {0 0 0 1} of β-Si3N4 is preferentially oriented in the X direction.
[0071] As shown in Table 2, it was found that the texture characteristics are differentiated between Examples 1 to 8 and Comparative Examples 1 to 3 by the area ratio of β-type silicon nitride crystal grains, which quantitatively indicates the characteristics of the pole figures. That is, in Examples 1 to 8, the area ratio of β-type silicon nitride crystal grains having a crystal orientation in which the inclination of the {1 0 -1 0} plane of the β-type silicon nitride crystal grains from the ND direction is within 70° is 90 to 98% for all β-type silicon nitride crystal grains, whereas it is outside that range in Comparative Examples 1 to 3. In Examples 1 to 8, the area ratio of β-type silicon nitride crystal grains having a crystal orientation in which the inclination of the {1 0 -1 0} plane of the β-type silicon nitride crystal grains from the ND direction is within 60° is 80 to 94% for all β-type silicon nitride crystal grains, whereas it is outside that range in Comparative Examples 1 to 3. In Examples 1 to 8, the area ratio of β-type silicon nitride crystal grains having a crystal orientation in which the {1 0 -1 0} plane of the β-type silicon nitride crystal grains is inclined from the ND direction by 50° or less is 65 to 85% for all β-type silicon nitride crystal grains, whereas it is outside that range in Comparative Examples 1 to 3. In Examples 1 to 8, the area ratio of β-type silicon nitride crystal grains having a crystal orientation in which the {1 0 -1 0} plane of the β-type silicon nitride crystal grains is inclined from the ND direction by 40° or less is 50 to 75% for all β-type silicon nitride crystal grains, whereas it is outside that range in Comparative Examples 1 to 3. In Examples 1 to 8, the area ratio of β-type silicon nitride crystal grains having a crystal orientation in which the {1 0 -1 0} plane of the β-type silicon nitride crystal grains is inclined from the ND direction by 30° or less is 30 to 52% for all β-type silicon nitride crystal grains, whereas it is outside that range in Comparative Examples 1 to 3.
[0072] As shown in Table 2, in Examples 1 to 8 and Comparative Examples 1 to 3, the thermal conductivities λx, λy, and λz are 70 W / mK or more. The ratio λz / λx of the thermal conductivity λx in the substrate molding direction to the thermal conductivity λz in the substrate thickness direction is 0.96 to 1.06 in Examples 1 to 8, but is outside that range in Comparative Examples 1 to 3. That is, the ratio of the difference between the thermal conductivity λz and the thermal conductivity λx to the thermal conductivity λx (|λz-λx| / λx) is 6% or less in Examples 1 to 8, but is 10% or more in Comparative Examples 1 to 3. In Examples 1 to 7, the difference ratio is 5% or less. In addition, the ratio λy / λx of the thermal conductivity λx in the substrate molding direction to the thermal conductivity λy in the perpendicular direction is 0.99 to 1.00 in Examples 1 to 8, but is outside that range in Comparative Examples 1 to 3. That is, the ratio of the difference between the thermal conductivity λy and the thermal conductivity λx to the thermal conductivity λx (|λy-λx| / λx) is 1.5% or less in Examples 1 to 8, whereas it is 1.9% or more in the Comparative Example. That is, the characteristic anisotropy of the thermal conductivity is significantly alleviated in Examples 1 to 8 compared to Comparative Examples 1 to 3.
[0073] As shown in Table 2, in Examples 1 to 8 and Comparative Examples 2 and 3, the bending strength σx in the substrate forming direction and the bending strength σy in the direction perpendicular to the substrate forming direction are 600 MPa or more. In Comparative Example 1, the bending strengths σx and σy are less than 600 MPa, which does not satisfy the standard strength. The ratio σy / σx of the bending strength σx and the bending strength σy is 0.9 to 1.1 in Examples 1 to 8, but is outside that range in Comparative Examples 2 and 3. That is, in the ratio of the difference between the bending strength σx and the bending strength σy to the bending strength σx (|σy-σx| / σx), the ratio is 10% or less in Examples 1 to 8, but is greater than 10% in Comparative Examples 2 and 3. That is, Examples 1 to 8 have the desired bending strength, while the characteristic anisotropy of the mechanical strength is significantly alleviated compared to Comparative Examples 2 and 3.
[0074] Furthermore, as shown in Table 2, the intensity ratio I(002) / I(200) of the integrated intensity I(002) to the integrated intensity I(200) of the X-ray diffraction peak is 0.05 to 0.2, whereas it is outside that range in Comparative Examples 2 and 3. That is, it is possible to differentiate Examples 1 to 8 from Comparative Examples 1 to 3 also by structural analysis using X-ray diffraction.
[0075] The present invention is not limited to the above-described embodiment, and can be embodied in various forms within the technical scope of the present invention. [Explanation of symbols]
[0076] 10 Semiconductor device 11 Insulated circuit board 13. Sintered silicon nitride 15 metal plate 17 Semiconductor elements
Claims
1. A silicon nitride sintered body comprising a substrate having an RD direction and a TD direction perpendicular to each other in a plane perpendicular to an ND direction of the substrate thickness direction, the RD direction being defined as a rolling direction of a green sheet of the silicon nitride sintered body; A silicon nitride sintered body, characterized in that the bending strength σx in the RD direction and the bending strength σy in the TD direction perpendicular to the RD direction are each 600 MPa or more, and the ratio of the difference between the bending strength σx and the bending strength σy to the bending strength σx (|σy-σx| / σx) is 10% or less.
2. The silicon nitride sintered body according to claim 1, characterized in that the ratio (|λz-λx| / λx) of the difference between the thermal conductivity λz in the substrate thickness direction and the thermal conductivity λx in the RD direction to the thermal conductivity λx in the RD direction is 6% or less.
3. 3. An insulating circuit board comprising: the silicon nitride sintered body according to claim 1 or 2; and a metal plate bonded to a surface of the silicon nitride sintered body.
4. A semiconductor device comprising: the insulating circuit board according to claim 3; and a semiconductor element mounted on a metal plate of the insulating circuit board.
Citation Information
Patent Citations
High strength and high toughness silicon nitride sintered compact
JP1996143400A
Semiconductor module
JP1998150125A
Molding product for sintered silicon nitride having high heat conductivity, its production, sintered silicon nitride having high heat conductivity and its production
JP2000103680A
Silicon nitride powder and its production
JP2000178013A
Silicon nitride sintered substrate, electronic apparatus, and method for manufacturing the silicon nitride sintered substrate
JP2019052072A